Induction of iNOS expression and antimicrobial activity by interferon (IFN)-β is distinct from IFN-γ in Burkholderia pseudomallei-infected mouse macrophages - UTAISINCHAROEN, P (Blackwell Science Inc, 2004)
Burkholderia pseudomallei is a causative agent of melioidosis. This Gram-negative bacterium is able to survive and multiple inside both phagocytic and nonphagocytic cells. We previously reported that exogenous interferons (both type I and type II) enhanced antimicrobial activity of the macrophages infected with B. pseudomallei by up-regulating inducible nitric oxide synthase (iNOS). This enzyme thus plays an essential role in controlling intracellular growth of bacteria. In the present study we extended our investigation, analysing the mechanism(s) by which the two types of interferons (IFNs) regulate antimicrobial activity in the B. pseudomallei-infected macrophages. Mouse macrophage cell line (RAW 264·7) that was exposed simultaneously to B. pseudomallei and type I IFN (IFN-β) expressed high levels of iNOS, leading to enhanced intracellular killing of the bacteria. However, neither enhanced iNOS expression nor intracellular bacterial killing was observed when the macrophages were preactivated with IFN-β prior to being infected with B. pseudomallei. On the contrary, the timing of exposure was not critical for the type II IFN (IFN-γ) because when the cells were either prestimulated or co-stimulated with IFN-γ, both iNOS expression and intracellular killing capacity were enhanced. The differences by which these two IFNs regulate antimicrobial activity may be related to the fact that IFN-γ was able to induce more sustained interferon regulatory factor-1 (IRF-1) expression compared with the cells activated with IFN-β.